Molecular characteristics and antibiotic resistance mechanisms of multidrug-resistant Pseudomonas aeruginosa in Nanning, China - Xianzhen Wei; Mingbo Liu; Cuiju Mo; Runxian Tan; Shan Li; Hongjie Liang; Meng Li (BMC Microbiology)
Abstract Purpose This study analyzed antibiotic resistance mechanisms and molecular epidemiology of multidrug-resistant Pseudomonas aeruginosa (MDR-PA), aiming at providing clues for prevention and control of MDR-PA infections. Methods The carbapenemase resistance genes (VIM, IMP, NDM, KPC, GES, OXA-40) of MDR-PA strains were detected by polymerase chain reaction (PCR) and sequencing. The efflux pump system (MexA, MexC, MexE, MexX), AmpC and OprD2 were detected by real-time fluorescent quantitative PCR (qPCR) in MDR-PA group and sensitive-Pseudomonas aeruginosa (S-PA) group. The homology analysis of MDR-PA strains was performed by multilocus sequence typing (MLST). Results A total of 81 MDR-PA strains were collected from the First Affiliated Hospital of Guangxi Medical University from October 2022 to October 2023. Among the carbapenemase detected, the detection rate of NDM-1 was the highest, with a rate of 34.57% (28/81). MexA had a higher expression in MDR-PA group than that in S-PA group (P<0.0001). 81 MDR-PA strains belonged to 40 different ST types, mainly including ST1971, ST244, ST357 and ST308, and the predominant ST type was ST1971 (34.57%, 28/81). Conclusion The mechanisms of antibiotic resistance of MDR-PA strains mainly were the production of MBLS and higher expression of MexA in our study, and ST1971 was the predominant ST type of MDR-PA strains in our hospital, our findings may assist in prevention and control of MDR-PA infections.